FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN PERAWAT DALAM DOKUMENTASI PENGKAJIAN NYERI PQRST BERBASIS ELECTRONIC MEDICAL RECORD (ERM) DI RAWAT INAP DEWASA RS X BSD - Nober Ompusungu; Maria Lousiana; Fendy Yesayas (NHM PRESS, 2022)
Pain assessment is an effort to overcome pain that is carried out in infants, children, adults and sedated with medication (pharmacology) or without drug administration (non-pharmacological) according to the level of pain felt by the patient. knowledge and motivation related to nurse compliance in PQRST pain assessment documentation based on Electronic Medical Record (EMR) at RS X BSD's adult inpatient. This type of research uses quantitative research methods, with a descriptive correlation research design and uses a cross sectional approach. Sampling using total sampling technique. Research respondents amounted to 60 people. Data analysis using Kendal Tau statistical test b. The results showed a relationship between the age factor (p-value 0.551), education factor (p-value 0.579), the tenure factor (p-value 0.001), so it can be concluded that the characteristics of nurses (education) are mostly Diploma three who are advocacy nurses. knowledge factor (p-value 0.007) that in general nurses' knowledge is quite good in conducting pain assessments, motivational factor (p-value 0.044) concluded that there are still nurses who have low motivation in conducting PQRST pain assessments according to hospital SPO because of personal constraints, namely less understand the EMR-based PQRST pain assessment, forgetfulness, space hassles and commitments, supervision of the ward head has not been routinely carried out. It is expected that RS X Hospital will provide formal training on pain assessment, form a pain assessment team and periodic audits of EMR-based PQRST pain assessment documentation